New fossils of Sphaeriusidae from mid-Cretaceous Burmese amber revealed by confocal microscopy (Coleoptera: Myxophaga) - Li, Yan-Da; Ślipiński, Adam; Huang, Di-Ying; Cai, Chen-Yang (Frontiers in Earth Science, 2023)
Sphaeriusidae is a small family of tiny aquatic beetles in the suborder Myxophaga. In this study we characterize two new sphaeriusid fossils from the mid-Cretaceous Burmese amber with the help of confocal laser scanning microscopy. Sphaerius martini Li & Cai sp. nov. displays similarities with both extant Bezesporum and Sphaerius, although it can be readily recognized based on the parallel-sided prosternum. Crowsonaerius minutus Li & Cai gen. et sp. nov. differs from other genera of Sphaeriusidae in having unreduced apical maxillary palpomeres, lowered mesoventrite, large metacoxal plates, separated mesotrochanter and mesofemur, and equal pretarsal claws. The present study demonstrates the efficacy of confocal microscopy in studying minute and dark bioinclusions in amber.urn:lsid:zoobank.org:pub:6E6EDC20-744A-4A75-849A-4B6126628C15.